IMPACT OF USE OF TECHNOLOGY IN MATHEMATICS LESSONS ON STUDENT ACHIEVEMENT AND ATTITUDES - Eyyam, Ramadan; Yaratan, Huseyin S. (Soc Personality Res Inc, 2014)
Technology use in classrooms in today's world is believed to have a positive impact on students' success and their attitudes towards lessons. In this study we investigated students' attitudes towards technology use in class and whether the use of technology improved their academic achievement. A quasiexperimental research design was used and we assigned 3 groups as experimental groups (n = 41) and 2 as control groups (n = 41). Mathematics was selected as the subject to be studied. All groups completed a pretest and a posttest. For the experimental groups, lessons were designed using several technological tools, whereas lessons for control groups were taught using traditional teaching methods. At the end of the study, the experimental groups completed a scale to investigate the preferences and attitudes of the students in regard to technology-based instruction. One-way ANCOVA was used to evaluate the differences in posttest results, which revealed that the mathematics posttest results of the students who were instructed using technology were significantly higher than the posttest results of the groups who were instructed without technology. Results showed that students had a positive attitude towards technology use. The implications for curriculum designers and teachers are discussed.
Keywords: achievement; attitude; quasiexperimental research design; mathematics; technology use